2011
DOI: 10.1007/s10815-011-9595-8
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol supplementation during the luteal phase in poor responder patients undergoing in vitro fertilization: a randomized clinical trial

Abstract: Purpose This study was designed to evaluate the effects of adding Estradiol (E2) supplementation to progesterone (P) on improvement of pregnancy outcomes in poor responder patients who underwent in vitro fertilization (IVF).Methods In a prospective randomized clinical trial, 118 poor responder patients, older than 38 years without contraindications of estradiol consumption from Infertility clinic of a university hospital were randomly divided (by computerized software) into two groups. Control group (59 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…The authors found that the E2 supplementation was associated with sig- nificant decrease in E2 levels after hCG injection when compared to placebo. However the clinical pregnancy rate and number of retrieved oocytes were not affected by the E2 supplementation, which is consistent with previous studies [23,24]. The results showed that E2 serum levels in hCG administration day and the third and seventh day after ovum retrieval in these patients were noticeably decreased.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The authors found that the E2 supplementation was associated with sig- nificant decrease in E2 levels after hCG injection when compared to placebo. However the clinical pregnancy rate and number of retrieved oocytes were not affected by the E2 supplementation, which is consistent with previous studies [23,24]. The results showed that E2 serum levels in hCG administration day and the third and seventh day after ovum retrieval in these patients were noticeably decreased.…”
Section: Discussionsupporting
confidence: 91%
“…Histological data from endometrial biopsies of patients undergoing IVF on days 21 and 25 of cycles has shown that omitting the E2 injections from treatment cycles does not have any effects on unity of uterine endometrium, estrogen receptor numbers, and hormone profile of these patients. In these studies, it has been suggested that perhaps the high physiologic levels of progesterone compensates for loss of E2 during the midluteal phase and masks its effects on unity of endometrium, embryo implantation, and as a result the outcome of IVF [24]. In addition, it has been suggested that since the optimal dose of E2 administration during the luteal phase is still not determined and is of question, perhaps the reason for controversial results on this subject is due to ineffectiveness of E2 supporting doses during the luteal phase [5].…”
Section: Discussionmentioning
confidence: 99%
“…The use of E 2 in daily doses of 4 to 6 mg/day to improve the luteal phase is a controversial topic. Fatemi et al (2007) , Ceyhan et al (2008) , Aghahosseini et al (2011) , Lin et al (2013) and Engmann et al (2008) in randomized studies, reported no benefit stemming from the administration of E 2 in a dose of 4 mg/day. Other authors ( Drakakis et al.…”
Section: Discussionmentioning
confidence: 98%
“…Aghahosseini и соавт. [37] первыми провели рандомизированное контролируемое исследование влияния приема препаратов эстрогенов (4 мг перо-рально) в лютеиновую фазу цикла ЭКО у 118 паци-енток старше 37 лет, у которых было получено 5 и менее ооцитов. Авторы не выявили различий в ча-стоте имплантации и частоте наступления беремен-ности между группами, которые в данной когорте пациенток оказались чрезвычайно низкими (9,5% против 8,2% и 13,2% против 10,9% соответственно).…”
Section: влияние уровня эстрадиола на исход экоunclassified